Drugs, thugs, and divas : telenovelas and narco-dramas in Latin America - Benavides, O. Hugo (Oswald Hugo), 1968- (University of Texas Press, 2008)
Soap opera speaks a universal language, presenting characters and plots that resonate far beyond the culture that creates them. Latin American soap operas--telenovelas--have found enthusiastic audiences throughout the Americas and Europe, as well as in Egypt, Russia, and China, while Mexican narco-dramas have become highly popular among Latinos in the United States. In this first comprehensive analysis of telenovelas and narco-dramas, Hugo Benavides assesses the dynamic role of melodrama in creating meaningful cultural images to explain why these genres have become so successful while more elite cultural productions are declining in popularity. Benavides offers close readings of the Colombian telenovelas Betty la fea (along with its Mexican and U.S. reincarnations La fea mas bella and Ugly Betty), Adrian esta de visita, and Pasion de gavilanes; the Brazilian historical telenovela Xica; and a variety of Mexican narco-drama films. Situating these melodramas within concrete historical developments in Latin America, he shows how telenovelas and narco-dramas serve to unite peoples of various countries and provide a voice of rebellion against often-oppressive governmental systems. Indeed, Benavides concludes that as one of the most effective and lucrative industries in Latin America, telenovelas and narco-dramas play a key role in the ongoing reconfiguration of social identities and popular culture. -- from publisher description.